Water Footprint Analysis of Oil Palm: (Case Study of the Pundu Region, Central Borneo) - Lisma Safitri; Valensi Kautsar; Sentot Purboseno; Retno Keksi Wulandari; Adhy Ardiyanto (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2018)
The rapid expansion of oil palm plantation areas in Indonesia is taking place every year. The impact is the emergence of various issues and opinions regarding the high environmental damage caused by excessive use of water by the crops. The water footprint scenario can be used to explain the usage of water for the oil palm. This is defined as the volume of water used to obtain one ton of fresh fruit bunches (FFB) in m3 yield-1 unit. The water footprint includes the green (water from precipitation), blue (water from surface and ground water resources) and grey water footprints (water used to dissolve fertilizers, pesticides and other chemical compounds). Based on these issues, this study was conducted to obtain the value of oil palm water footprint, in the case study area in Pundu, Central Borneo. Data used include climate, FFB production and the use of fertilizers and pesticides. The results show that the water footprint of oil palm is 1002.1 m3 ton-1 with the following plantation conditions: productivity was about 13.41 ton ha-1, the use of fertilizer was 0.12 ton ha-1, irrigation was assumed only given to pre-nursery and nursery activities. The green, blue, and grey water footprints was 876.7, 35.9 and 89.5 m3 ton-1, respectively. The oil palm in the research area were grown with the main source of water coming from precipitation, not from groundwater (blue WF is only 3.6% of total WF). The Grey WF was 8.9 % which is lower than the average Grey WF of oil crops worldwide.